CLINICAL ASSESSMENT OF HYPERPIGMENTATION IN THE THIRD TRIMESTER OF PREGNANCY IN RELATION TO FETAL GENDER, SKIN TYPE AND MATERNAL AGE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background Hyperpigmentation, caused by increased serum levels of MSH, oestrogen, or progesterone, is the most prevalent pregnancy symptom. Progesterone, which is a byproduct of melanin deposition into dermal and epidermal macrophages, enhances the impact of oestrogen, which in turn increases the output of melanin by the melanocytes. While hyperpigmentation can happen everywhere, it usually shows up darker in naturally darker areas, including the inner thighs, periumbilical area, areolas (sometimes called "secondary areolas"), nipples, genitalia, and axillae.
Keywords: Hyperpigmentation, Maternal age , skin, gender, third trimester.